The Signal Transduction Protein P(II) Controls Ammonium, Nitrate and Urea Uptake in Cyanobacteria - Watzer, Björn (Front Microbiol, 2019)
P(II) signal transduction proteins are widely spread among all domains of life where they regulate a multitude of carbon and nitrogen metabolism related processes. Non-diazotrophic cyanobacteria can utilize a high variety of organic and inorganic nitrogen sources. In recent years, several physiological studies indicated an involvement of the cyanobacterial P(II) protein in regulation of ammonium, nitrate/nitrite, and cyanate uptake. However, direct interaction of P(II) has not been demonstrated so far. In this study, we used biochemical, molecular genetic and physiological approaches to demonstrate that P(II) regulates all relevant nitrogen uptake systems in Synechocystis sp. strain PCC 6803: P(II) controls ammonium uptake by interacting with the Amt1 ammonium permease, probably similar to the known regulation of E. coli ammonium permease AmtB by the P(II) homolog GlnK. We could further clarify that P(II) mediates the ammonium- and dark-induced inhibition of nitrate uptake by interacting with the NrtC and NrtD subunits of the nitrate/nitrite transporter NrtABCD. We further identified the ABC-type urea transporter UrtABCDE as novel P(II) target. P(II) interacts with the UrtE subunit without involving the standard interaction surface of P(II) interactions. The deregulation of urea uptake in a P(II) deletion mutant causes ammonium excretion when urea is provided as nitrogen source. Furthermore, the urea hydrolyzing urease enzyme complex appears to be coupled to urea uptake. Overall, this study underlines the great importance of the P(II) signal transduction protein in the regulation of nitrogen utilization in cyanobacteria.